Oñati Proceedings: Legal culture and everyday life - García Ramos, José Ignacio (dir.) (1989)
Contiene: Sociology of law and legal practitioners; Science et action: Quelques reflexions sur les relations Recherche-Practiciens du Droit; Sociology of law and legal practice; The new social contract: Institutions and social movements; Civil professio nalism; Towards a postmodern understanding of law; Toward a truly international sociology of law through the study of the legal pluralism existing in the world.